Step-by-step explanation:
First we need to convert the sentence to an algebraic expression
We will break down the parts to do so:
sum of 6 and some number
let the number = n
sum means we will be adding 6 to the number
So, sum of 6 and some number = 6 + n
5 times the sum: this means we will multiply the sum we got above by 5
5 times then sum of 6 and some number = 5(6 + n)
five times the sum of 6 and some number is 20:
This means the multiplication of the sum by 5 equals to 20
So, the final algebraic expression:
5(6 + n) = 20
Next, we will solve for the unknown number which is n in this case:
5(6 + n) = 20
expand the parenthesis:
5(6) + 5(n) = 20
30 + 5n = 20
subtract 30 from both sides:
30 - 30 + 5n = 20 - 30
5n = -10
divide both sides by 5:
5n/5 = -10/5
n = -2
Hence, the unknown number is -2